Penatalaksanaan Holistik Pada Anak Usia 9 Tahun Dengan Tonsilitis Kronis Melalui Pendekatan Kedokteran Keluarga - Djuardi, Attisya Milenty Putri; Mayasari, Diana (CV. Jasa Sukses Abadi, 2023)
Tonsillitis can occur at any age, especially in children. Tonsillitis has become one of the causes of decreased academic achievement and absenteeism from school. Patients with tonsillitis are also patients who often come to the practice of ear, nose, throat, head and neck surgeons (ENT-KL), pediatricians, and other health care facilities. This case report describes a 9 year old child who complained of fever accompanied by cold, cough, pain of swallowing, bad breath, and snoring. Patients often experience this complaints at least once every two months. Local status examination revealed a hyperemic pharynx, enlarged T3-T2 tonsils, widened crypts (+/+), detritus (+/+), and an uneven surface. The management provided is in the form of medical and non-medical therapy as a holistic intervention with a family medicine approach. The aim of this article is to identify risk factors, clinical problems, and management using a patient centered and family approach. This study is a case report. Primary data was obtained through history taking, physical examination and home visits.. As a result of this study, the patient was diagnosed with chronic tonsillitis. Internal risk aspects that influence the patient's condition include the patient's age, patient’s knowledge, patient’s lifestyle, dental and oral hygiene, and poor diet. External risk aspects that influence the patient's condition include a lack of family supervision regarding the patient's snack consumption, and slow decision making regarding follow-up actions based on patient complaints, the patient's family does not know enough about patient’s disease. Furthermore, holistic management has been carried out for patients and families through colored poster intervention media in the form of information about diseases, triggers and complications.